Developing Web-Based Accounting Information System on Sharia-Based Auction Company - Pebriadi, Muhammad Syahid; Ade Yulia Sari; Heldalina; Muhammad Hendra Sunarya; Phaureula Artha Wulandari (Indonesian Journal of Applied Accounting and Finance, 2024)
This article explores the development of a web-based accounting information system (AIS) for a sharia-based auction company. The aim was to streamline operational workflows, enhance financial reporting transparency, and automate complex financial transactions, ensuring compliance with sharia principles. The research method involved multiple stages, including requirement analysis, system design, system development, and evaluation. The successful implementation of the system led to improved efficiency, accuracy in financial reporting, and real-time insights for decision-making. Additionally, compliance checks confirmed the system’s adherence to sharia standards. The integration of modern technology with traditional ethical practices has enabled the company to uphold sharia principles while achieving operational excellence. This article provides insights into the benefits and challenges of developing and implementing a web-based accounting system in a sharia-based auction company, offering valuable lessons for similar initiatives in the industry.